2020
DOI: 10.47839/ijc.19.4.2000
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Graph Based Term Expansion for Sentence-Level Sentiment Analysis

Abstract: The semantic orientation (also referred to as prior polarity) of a word plays an important role in automatic sentence-level sentiment analysis. Several approaches have been proposed wherein a lexicon of words marked with their polarities is exploited to infer the meaning of sentences. However, relying on prior word polarity may produce inaccurate decisions. This is because we may find negative-sentence sentiments that include words with positive prior polarities or vice versa. In this article, we propose an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, other studies showed that coupling bigrams and trigrams based on extrinsic semantic resources provided better results than unigrams alone [2], [18]. As reported by Maree and Eleyat in [2], incorporating high-order ngrams such as trigrams that can be acquired based on external knowledge resources captures a sentence contextual information more precisely than other unigram or bigram-based tokenizers. Accordingly, and in light of these conclusions, it is crucial to experimentally evaluate the utilization of n-gram tokenization as part of the large-scale SA process.…”
Section: Tokenization and Feature Extractionmentioning
confidence: 94%
See 4 more Smart Citations
“…On the other hand, other studies showed that coupling bigrams and trigrams based on extrinsic semantic resources provided better results than unigrams alone [2], [18]. As reported by Maree and Eleyat in [2], incorporating high-order ngrams such as trigrams that can be acquired based on external knowledge resources captures a sentence contextual information more precisely than other unigram or bigram-based tokenizers. Accordingly, and in light of these conclusions, it is crucial to experimentally evaluate the utilization of n-gram tokenization as part of the large-scale SA process.…”
Section: Tokenization and Feature Extractionmentioning
confidence: 94%
“…Sources of sentiment sentences can vary on the Web. Twitter and other social media websites are among the most commonly referred to sources [2]. For experimental evaluation purposes, we use the wellknown internet movie database (IMDB) movie reviews dataset, which is publicly available at Kaggle.…”
Section: Data Acquisition and Cleansingmentioning
confidence: 99%
See 3 more Smart Citations